1995
DOI: 10.1016/0896-6273(95)90146-9
|View full text |Cite
|
Sign up to set email alerts
|

Receptor tyrosine kinase specific for the skeletal muscle lineage: Expression in embryonic muscle, at the neuromuscular junction, and after injury

Abstract: While a number of growth factors have been described that are highly specific for particular cell lineages, neither a factor nor a receptor uniquely specific to the skeletal muscle lineage has previously been described. Here we identify a receptor tyrosine kinase (RTK) specific to skeletal muscle, which we term "MuSK" for muscle-specific kinase. MuSK is expressed at low levels in proliferating myoblasts and is induced upon differentiation and fusion. In the embryo, it is specifically expressed in early myotome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
353
1
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 397 publications
(386 citation statements)
references
References 33 publications
27
353
1
5
Order By: Relevance
“…In wild-type mice, Musk mRNA and protein are concentrated at neuromuscular synapses (Valenzuela et al, 1995). In Musk mutant mice carrying MCK-Musk, Musk mRNA is expressed throughout the muscle, yet Musk protein is concentrated at synaptic sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wild-type mice, Musk mRNA and protein are concentrated at neuromuscular synapses (Valenzuela et al, 1995). In Musk mutant mice carrying MCK-Musk, Musk mRNA is expressed throughout the muscle, yet Musk protein is concentrated at synaptic sites.…”
Section: Discussionmentioning
confidence: 99%
“…In wild-type mice, Musk RNA, like AChR mRNA, is expressed preferentially at synaptic sites (Valenzuela et al, 1995). Because the MCK gene is expressed in nuclei throughout the myofiber (Tang et al, 1994), the MCK regulatory region, as expected, confers Musk and MMT mRNA expression uniformly throughout the muscle (Fig.…”
Section: Musk and Mmt Proteins Are Concentrated At Synaptic Sites Desmentioning
confidence: 94%
“…These studies implicated motor neuron-derived Agrin, a glycosylated proteoglycan, as the critical neural signal for inducing postsynaptic differentiation and the muscle-specific receptor tyrosine kinase, MuSK, a component of the Agrin receptor, as the transducer for clustering AChRs and activating AChR gene expression at synaptic sites (Burden, 1998;Glass et al, 1996a;Glass et al, 1996b;Glass and Yancopoulos, 1997;Sanes and Lichtman, 2001;Schaeffer et al, 2001;Valenzuela et al, 1995). This neuro-centric view of neuromuscular synapse formation, however, has been challenged by recent experiments, which showed that mammalian muscle is spatially patterned independent of innervation.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian Ror2 and the closely related paralog Ror1 belong to a small family of receptor tyrosine kinases (RTKs) that have been characterized by their homology to MuSK and TrkRTKs (Masiakowski and Carroll, 1992;Valenzuela et al, 1995). Ror2 possesses an intracellular tyrosine kinase domain and a C-terminal proline-serine-threonine-rich (PST) domain.…”
Section: Introductionmentioning
confidence: 99%